'Our time is precious': An exploration of parental feeding behaviours for boys with Duchenne muscular dystrophy. (3rd September 2022) - Walker, Meaghan; McAdam, Laura; Amin, Reshma; Lui, Toni; McPherson, Amy C.
Abstract: Introduction: Due to the increased risk of obesity for boys with Duchenne muscular dystrophy (DMD), recent guidelines recommend that dietary intake is carefully managed. Parents play an important role in the development of their child's eating behaviours and patterns. However, despite what is known about the increased risk of obesity for children with DMD, little is known about parental feeding behaviours in this population. The objective of this study was to qualitatively explore the experiences of parents of children with DMD around their child's weight management and understand what influences their feeding behaviours. Methods: This paper reports a secondary data analysis. Semi‐structured, individual interviews were conducted and analysed using qualitative description. Results: Thirteen parents were interviewed for the study. Three themes were developed: (1) parent responses to healthcare provider interactions, (2) mixed emotions contributing to feeding approach and (3) variable parenting feeding styles. Within the third theme, two subthemes arose including (1) control and preoccupation and (2) striking a balance. Conclusion: Given the potential impact of higher weights on the progression of DMD, it is important that healthcare providers explore feeding behaviours with families. However, it is essential that healthcare providers consider the impact of these conversations on parents, as well as the broader issues that may place additional pressure on the lives of families.